Conformational flexibility of beta-secretase: molecular dynamics simulation and essential dynamics analysis - XIONG Bing; HUANG Xiao-qin; SHEN Ling-ling; SHEN Jian-hua; LUO Xiao-min; SHEN Xu; JIANG Hua-liang; CHEN Kai-xian (Acta Pharmacologica Sinica; Vol 25, No 6 (June 2004): Acta Pharmacologica Sinica, 2016)
AIM: Based on the structural analysis to reveal the mechanism of ligand binding to beta-secretase and the specificity of each binding sub-site. METHODS: Molecular dynamics was used to simulate on the ligand free beta-secretase and ligand bound beta-secretase. The trajectories were analyzed using the essential dynamics, and the significant conformational change was illustrated employing the DynDom program. RESULTS: The essential dynamics and DynDom analyses clearly showed that the beta-secretase experienced a large conformational change upon the substrate or inhibitor binding. The flap structure adopted a swing motion, gradually covering the active site to facilitate the ligand binding process. Residues Ser86 and Ile87 served as the hinge point. Inhibitor-enzyme interaction analysis revealed that residues at P2, P1, and P1' positions of the inhibitor were very important for the binding, and residues at P2' and P3' positions may be modified to improve the binding specificity. S3 subsite of the enzyme still had space to modify the inhibitors in increasing the binding affinity. CONCLUSION: The information presented here is valuable and could be used to identify small molecular inhibitors of beta-secretase.